Balto: comedic representation of medical professionals in TV drama - May Soliman (Philosophy, Ethics, and Humanities in Medicine)
Abstract Medical professionals have been portrayed as hard-working and serious individuals in most Egyptian dramas. Recent Egyptian TV series have portrayed medical service providers, highlighting different aspects of their personalities. The present paper adopts an approach that combines the studies of humor and language to investigate the comedic representation of medical professionals in contemporary Egyptian television TV drama, with special reference to a recent TV series called Balto (2023). Within the framework of humor theories of incongruity and superiority, this paper aims to analyze elements of the comedic portrayal of health professionals in the selected TV series, Balto, to investigate how humor is employed to both humanize the long-idealized depiction of doctors as well as critique societal perceptions of representatives of the medical sector in Egypt. The paper particularly focuses on analyzing how the protagonist and other medical professionals practice their work, exercise managerial power, and operate/function with their peers and patients within a small remote health unit.